IS IT CONVENIENT FOR AN ENTERPRISE TO FALL INTO DEBT WITH A BANK? - Santos Jiménez, Néstor (2007)
Enterprises count on multiple financing alternatives which deserve to be analized in order to come out the most suitable combination between a debt and the shareholder(or shareholders) capital contribution. The financial model based on VPN as a decision criterium helps to select the best financial alternative with a debr. Banking debt improves the enterprise's value, but a balance between indevtedness and aown capital is required. Banking debt can be convenient as interest rate goes below the shareholder's opportunity cost. Debt benefit for the shareholder shows up when the enterprise enters financial expenditures in determinig workers share within the enterprise's utilities and the SUNAT's income tax payment in the books.